Stress Strain Behaviour of Solid Block Masonry Prism under Axial Compression - E, Kavitha; C, Vinodhini; R, Elavarasan; R, Udhayasakthi (International Research Journal of Multidisciplinary Technovation, 2024)
Masonry is possibly the primary construction element currently in widespread use throughout the world. Load-bearing masonry building is prevalent in developing countries for home construction. When properly constructed, masonry is frequently a more cost-effective and energy-efficient alternative to reinforced concrete for wall building. In addition to performing the dual roles of supporting weight and enclosing space, structural masonry boasts a high level of fire resistance, thermal and acoustic insulation, and exposure protection. The remarkable durability and low maintenance costs are further evident benefits. Masonry has a significant role in building construction, particularly in structures, as it is regarded as the primary component of the building. The eco-friendly solid block is prepared by adding the following by-products like coal ash, granite powder, olivine sand etc., all these ingredients used for manufacturing the solid block are waste materials from various industries. Thus, extensive testing is necessary to assess their load carrying capacity and secant modulus accurately. Masonry prisms were developed with five-layer solid blocks and tested for their stress-strain characteristics and secant modulus and the test outcomes were compared with conventional fly ash cement blocks. Eco-friendly solid blocks offer a persuasive substitute for ecologically conscious approaches to building by preserving structural integrity and functionality while promoting sustainability.